Republic of Armenia : Request for Stand-By Arrangement-Staff Report; Staff Supplements and Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for the Republic of Armenia. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
This paper discusses Armenia's request for a Stand-By Arrangement (SBA) with exceptional access of 400 percent of quota. Given the urgency of the situation, the request is being considered under the Emergency Financing Mechanism. The new program aims to achieve the necessary external adjustment, restore confidence in the domestic currency and the banking sector, and protect the poor. The authorities have also committed to a set of policies in the exchange rate, monetary and financial, and fiscal areas as well as on maintaining its ongoing structural reform program.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet